Immediate effect of kinesio taping on knee extensor torque of children with Cerebral Palsy: Three case reports. - dos Santos, Adriana Neves; Rocha, Nelci Adriana Cicuto Ferreira (NeuroRehabilitation, 2018)
BACKGROUND: Kinesiotaping (KT) has been commonly used in clinical setting. However, beneficial KT effects have not been proved yet. OBJECTIVE: We aimed to verify the effects of KT in knee extensor torque in children with CP. METHODS: We evaluated three children diagnosed as spastic CP, classified as level I, II and III, according with GMFCS. Knee extensor peak torque was analyzed by isokinetic evaluation (Biodex Multi Joint System). The test was performed at 603/s in the concentric passive mode and the children performed maximal contractions. Children with CP were evaluated with and without KT under rectus femoris. RESULTS: After KT application, knee peak torque of the affected limb increased in children with CP. CONCLUSION: KT may increase muscle strength in children with CP.